The use of the SWARA method for the selection of cryptocurrency hardware - Trišić Marko (Trendovi u Poslovanju)
The use of mathematical programming has become an everyday occurence in the process of making major management decisions. In such cases, the decision making methods can serve as tools being used to make effective decisions and also repair the incorrect ones. The phenomenon of cryptocurrencies is being increasingly imposed, from informal conversations through thoughtful investment projects. One of the key issues that should be solved before entering such a type of entrepreneurship are computer components (hardware) that will predestine the comfort and expediency of working with cryptocurrencies. In order to provide a credible presentation for one of the multi-criteria decision-making methods, this paper displays a practical application of the SWARA method - being used in cryptomining. The task setup and results are based on real-life examples.